3D FEM Analysis of the Buckling Delamination of a Rectangular Viscoelastic Composite Plate with an Embedded Rectangular Crack Under Two-Axial Compression - Akbarov, S. D.; Yahnioglu, N.; Karatas, E. E. (TECH SCIENCE PRESS, 2012)
In Akbarov, Yahnioglu and Karatas (2010) a buckling delamination problem for a rectangular viscoelastic composite plate with a band and edge cracks was investigated under uniaxial compression of the plate. In the present study this investigation is developed for the case where the mentioned rectangular plate contains an embedded rectangular crack and in addition it is assumed that the plate is subjected to two-axial compression. It is supposed that all end surfaces of the considered plate are simply supported and that these ends are subjected to uniformly distributed normal compressive forces with intensity p(1) and p(3) which act along the Ox(1) and Ox(3) axes, respectively. Moreover, we assume that the plate contains a rectangular embedded crack, the edge-surfaces of which have initial infinitesimal imperfections before the loading. The evolution of these initial imperfections with time under two-axial compression of the plate is studied within the framework of the three-dimensional geometrically nonlinear field equations of the theory of viscoelasticity for anisotropic bodies. For determination of the values of the critical force or of the critical time, as well as those of the buckling delamination mode of the considered plate, the initial imperfection criterion is used. For the solution to the corresponding boundary-value problems, boundary form perturbation techniques; the Laplace transform; the Schapery method for obtaining the numerical inverse Laplace transform of the sought values; and the 3D FEM are used. The numerical results of the critical force and critical time, as well as of the buckling delamination modes are presented and discussed.
Keywords: Buckling delamination; critical force; critical time; crack; rectangular plate; 3D finite element; viscoelastic composite material; STABILITY; FIBER; Computer Science; Materials Science